Morphological changes in liver of methimazole treated rats, a pilot study - Maira Bhatti; Waqas Iqbal Butt; Shahnaz Fatima; Fouzia Perveen; Sabeen Arjumand; Amna Iqbal Butt (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Thyrotoxicosis is a disease in which thyroid hormones are raised, and we have seen multiple patients suffering from this ailment in Pakistan. Methimazole is an anti-thyroid drug for thyrotoxicosis. Hepatotoxicity and liver ailments were common with methimazole prescribed for hypothyroid patients. Hypothyroidism, a common side effect of this drug, has been seen in a majority of patients, but liver toxicity remained unaddressed. So, in this study, we have observed histological changes in the liver after methimazole administration. METHODOLOGY: The pilot study was carried out in the University of Health Sciences (UHS), Lahore, and was ended in twenty-one days. We divided animals in 2 groups. Each group comprises 12 animals. Group-I was negative control, and water was given through the oral route for 21 days. Group-II was administered methimazole orally 60mg/kg/day for twenty-one days. At the end;S animals were dissected, and livers were removed for histological examination. RESULTS: The histological picture of the liver showed 75% severe disruption in liver architecture, inflammation, and fatty change in group 2, indicating liver damage. CONCLUSION: Methimazole, hepatotoxic with discernable damage to its architecture, epithelium, and inflammatory changes.